Kendiku Malang Kendiku Sayang Dalam Penciptaan Seni Kriya - Bagus Indrayana (Ornamen, 2008)
Environment is a place where all creatures live. It is very important to be rescued dan continuing all the beauty inside. It is wise to all especially craft men to responsible to keep it in a good and far away fom pollute. Besides, It is also wise to continuing the forefather culture and probably develop it. One of the way is to build creative effort by ming a synergy between old craft-manship and the condition of environment nowadays.Eventhough, there is no summary to all events and fenomena which occurred, because of many limitation, but the results of this study is proved that encourage the creativity among the young craftmen. This is shown that the old craftmanship and the condition of environment which move dynamic stimulate the power of imaginaion for the young craftmen to produce, creative and innovative.Key Word : craftmanship, creative, innovative kriya, kreatif,inovatif